2020
DOI: 10.3390/w12092366
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Groundwater Arsenic in Pampanga, Philippines

Abstract: Several confirmed cases of arsenic (As) poisoning have been reported in Central Luzon, the Philippines, in recent years. There is a growing interest in As research in the Philippines due to the reported As poisoning cases. However, an extensive spatiotemporal As study has not been conducted. In this work, As concentration measurements were conducted in 101 wells in Guagua, Pampanga, in Central Luzon, the Philippines, from November 2018 to November 2019. The wells included 86 public hand pumps, 10 pumping stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Solis et al conducted research on water samples from wells. The results revealed that 38.7% of the wells examined had arsenic concentration in excess of 10 µg/L, but not higher than 50 µg/L (average values) [65].…”
Section: Asiamentioning
confidence: 82%
“…Solis et al conducted research on water samples from wells. The results revealed that 38.7% of the wells examined had arsenic concentration in excess of 10 µg/L, but not higher than 50 µg/L (average values) [65].…”
Section: Asiamentioning
confidence: 82%
“…Our results agreed with other studies 58 , which found that pH varied between 7.5-9.9. In the current study area, pH variations may have occurred due to the minerals, pollutants, soil or bedrock composition, and other contaminants interacting with water 59 .…”
Section: Discussionmentioning
confidence: 97%